Multi-Fruit Tracking and 3-D Structure Recovery via CoTracker - Santos, Thiago Teixeira (Revista de Informática Teórica e Aplicada, 2026)
In agricultural robotics and orchard automation, tasks such as fruit detection, tracking, and spatial localization are essential for applications like yield prediction and harvesting. However, these tasks are challenging due to the similar appearance of fruits, occlusions, and the inherent difficulties of field robotics, including uncontrolled lighting conditions and the variability in orchard environments. This work leverages CoTracker, a transformer-based model for point tracking using cross-track/cross-time attention, to simultaneously perform multiple fruit tracking, 3-D fruit localization, and camera pose estimation. The proposed approach demonstrates promising results in fruit counting, tracking, and scene reconstruction, highlighting its potential in agricultural automation.